(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2025)
Today’s development of electronics mainly takes place in two directions. One direction is based on the technological development of semiconductor elements that will work in a larger current, voltage and frequency range. The other direction is based on the development of information bases and systems that will ensure the collection, visualization, processing and transport of process parameters. The first direction will enable applications in power electronics for higher powers and process speeds, and the second local and remote transmission of process data and their availability in intranet and internet networks. Taking this into account in the paper, an electronic system is designed and implemented that measures, stores and transmits the parameters of a 1-phase AC motor speed controller in an IoT network. The solution enables the visualization of input and output parameters locally on two LCD displays and remotely on an IoT device. A data log file is also provided for the measured values ​​on a local computer and on an IoT cloud computer.